Modified Lefort Distraction Osteogenesis for the Treatment of Nager Syndrome-Associated Midface Hypoplasia: Technique and Review. Issue 6 (September 2018) - Simpson, Andrew M.; Mehta, Sagar T.; Siddiqi, Faizi; Yamashiro, Duane; Gociman, Barbu
Abstract : Abstract: The surgical management of midface hypoplasia in the setting of Nager syndrome remains a significant challenge for craniofacial surgeons. This study describes a novel technique using distraction osteogenesis and modified osteotomies for the treatment of midface bony defects in an 11-year-old child with Nager syndrome. Presurgical 3-dimensional planning was performed to design the osteotomies and placement of distractors. The surgical approach required upper buccal sulcus and extended transconjunctival incisions only. Osteotomies were performed from the pyriform aperture through the orbit to include the lateral orbital wall, with bilateral osteotomy of the zygomas through the anterior arch via the transconjunctival incision. Distraction of the en bloc midface segment was successfully performed using external distractors. Bone grafting was not required. There were no complications. External distraction was well tolerated and there were no intraoperative or postoperative complications. The distractors were removed uneventfully after consolidation. The midface was successfully advanced without the need for bone grafting or bicoronal incision. The occlusal plane was leveled and the aesthetic appearance of the child was improved. Symmetrical midface hypoplasia in the context of Nager syndrome can be successfully corrected with en bloc distraction osteogenesis of the maxilla and bilateral zygomas through modified osteotomies that exclude the upper nasal pyramid. The approach is simplified and the need for bicoronal incision and bone grafting is mitigated in this technique, which the authors have named Lefort 2.5.